Current novel approaches in systemic therapy of atopic dermatitis. Issue 5 (October 2015) - Werfel, Thomas; Biedermann, Tilo
<x xml:space="preserve">Abstract</x> Purpose of review This present review gives an overview on different approaches on systemic treatment of atopic dermatitis with a focus on molecules that are presently investigated as defined target structures in clinical studies with patients with atopic dermatitis. Recent findings Available systemic drugs for the treatment of atopic dermatitis are limited. There is a high need for the development of new treatment regimen. Current studies address novel biologicals or small molecules for the treatment of atopic dermatitis. In particular, interventions in the T-helper 2 cell (Th2) allergic inflammation are promising. Dupilumab, a humanized monoclonal antibody to the interteukin-4R is the first antibody (i.e. 'biological') with published efficacy shown in controlled prospective studies in atopic dermatitis. A number of other target molecules is currently addressed in clinical studies with blocking antibodies against target molecules of Th2 polarized inflammation in atopic dermatitis (e.g. interleukins 13, 22, 31, thymic stromal lymphopoetin). Inhibiting phospodiesterase-4, chemoattractant receptor-homologous molecule 2, the histamine-4 receptor, or the neurokine-1 receptor may lead to the approval of novel 'small drugs' for a specific treatment of atopic dermatitis. Antifungals may be helpful in the variant of head and neck dermatitis associated with sensitizations against Malassezia species. Induction of specific immune tolerance (e.g. with allergen-specific immunotherapy) should be further studied in terms of the management of atopic dermatitis because available clinical studies resulted in inconsistent results on the skin condition. Summary Current studies with new substances for the systemic treatment of atopic dermatitis have tremendous implications for the future management of atopic dermatitis.